Comparison of tools for the creation of VLO for the subject of Algorithms. UTN case - Salazar-Fierro , Fausto; Herrera-Mayorga , Karla; Fernández , Cayo Léon; Pineda-Manosalvas, Carpio; Reascos , Irving (Data and Metadata, 2025)
This paper compares the performance of three authoring tools, eXeLearning, H5P and Xerte, used to create Virtual Learning Objects (VLOs). The research stems from the need to identify the most appropriate tool for creating VLOs. The study aimed to evaluate these tools through an objective comparison based on 15 pre-defined criteria. For this purpose, a methodological approach of the UP4VED methodology for virtual environments was used in addition to implementing the ADDIE methodology for developing VLOs. The results showed that eXeLearning achieved the highest score with 10.38 points, followed by Xerte with 8.83 and H5P with 7.74. Subsequently, DeLone & McLean's success model was applied to assess students' perceptions of using OVAs in an online course, with a minimum favourability index of 81.92% for quality of service and a maximum of 92.80% for quality of information. These results confirm the acceptability and effectiveness of OVAs as digital resources that enhance self-learning in educational environments.